Anomalous origin of the right coronary artery with interarterial course: red flag or innocent bystander?. (14th October 2021) - Albuquerque, F; De Araujo Goncalves, P; Ferreira, A; Lopes, P; Dores, H; Marques, H; Freitas, P; Goncalves, M; Cardim, N
Abstract: Aims: Anomalous origin of the right coronary artery from the opposite sinus (right-ACAOS) with interarterial course (IAC) has been associated with increased risk of sudden cardiac death (SCD). Widespread use of coronary computed tomography angiography (CCTA) has led to increasing recognition of this condition, even among healthy individuals. Our study sought to examine the prevalence, anatomical characteristics and outcomes of right-ACAOS with IAC in patients undergoing CCTA for suspected coronary artery disease (CAD). Methods and results: We conducted a retrospective analysis of consecutive patients referred for CCTA at one tertiary hospital from January 2012 to December 2020. Right-ACAOS with IAC patients were analyzed for cardiac symptoms and long-term occurrence of first MACE (SCD, non-fatal myocardial infarction (MI) or revascularization of the anomalous vessel). CCTAs were reviewed for anatomical high-risk features and concomitant CAD. Among 10928 patients referred for CCTA, 28 patients with right-ACAOS with IAC were identified. Mean age was 55±17 years, 64% were male and 11 (39.3%) presented with stable cardiac symptoms. Most patients had at least one high risk anatomical feature. During follow-up, there were no CV deaths or aborted SCD episodes and only 1 patient underwent surgical revascularization of the anomalous vessel. Conclusion: Right-ACAOS with IAC is an uncommon finding (prevalence of 0.26%). In a contemporary population of predominantly asymptomatic patients who survived this condition well into adulthood, most patients were managed conservatively with a low event rate. Additional studies are needed to support medical follow-up as the preferred option in this setting. Funding Acknowledgement: Type of funding sources: None.